PENGEMBANGAN EXPERIENTIAL LEARNING DENGAN METODE ELEMEN HINGGA PADA MATA KULIAH AERODINAMIKA - Muchlis Taufiq Anjar Wicaksono; Indah Widiastuti; Nugroho Agung Pambudi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
The study in Aerodynamics has shifted from large theoretical curriculum into authentic learning experiences in response to the industry requirement. In addition, the development of computational methods has revolutionized the design cycle in aerodynamics. This work describes an integrated approach in an undergraduate Aerodynamics course using the Kolb’s Learning cycle. Experiential learning is incorporated in the class to provide more opportunities for students to understand the theoretical concept through experiencing the applications and impact of the concept in real life. The Finite Element Method (FEM) which is widely used in analyzing many engineering problems was integrated into the Aerodynamics theory and application to visualize changes of parameter in the design phase. The main learning objective of the developed learning module is to apply appropriate aerodynamics models to predict the forces on and performance of a vehicle design. The module is assessed by instructor before being applied for the students in the classroom. It is considered to be an effective method for learning when lectures and computation works are integrated in a meaningful manner. This development research is expected to be able to produce graduates who are competent in the field of design.